Energy Use in Building in Front of Climate Change: An Analysis of the Adaptation Strategies of Corn Farmers in Benin - Miassi, Yann Emmanuel; Akdemir, Şinasi; Sengül, Haydar; Akçaöz, Handan; Dossa, Kossivi Fabrice (Journal of Agricultural Studies, 2024)
In Benin, maize production is important for food security and rural household incomes. However, it is subject to climatic variations that induce low yields and productivity levels. This innovative study categorizes the energy sources used in its production to identify levers for improving agricultural productivity. A survey of 230 maize growers in the communes of N'Dali, Sinende and Nikki was carried out. Data were collected using structured questionnaires on farming activities and input use, then converted into energy values using energy equivalence coefficients collected in previous studies. The results reveal a high level of awareness among maize growers (97.4%) of the impacts of climate change on maize production. In terms of the amount of energy derived from labor power, mechanical plowing stood out (133.02 MJ/ha), closely followed by animal-drawn plowing (53.04 MJ/ha) and harvesting (45.18 MJ/ha). In terms of inputs, NPK fertilizer stands out with an energy expenditure of 2238.87 MJ/ha, followed by urea with 1172.95 MJ/ha. Although increasing labor power remains the approach most adopted (61%) by growers to maintain the productivity of their farms, the results revealed a predominance of energy from agricultural inputs (94.91% of total energy), underlining the preponderance of inputs in overall energy requirements.